Quelle place pour l’historien dans le statut multiple des intellectuels latino-américains au début du xxe siècle ? Étude d’un cas - María Laura Reali (L'Atelier du CRH)
This paper deals with the interactions between the works of a historian and their context of production through the analysis of the case of Luis Alberto de Herrera (1873-1959), writer, historian and Uruguayan politician. Like many other public figures of the same period, this author has associated a retrospective reflection with a diagnosis of the current events of his country and he has extended his overall view towards larger geographical spaces. Besides, he has pursued an intense activity in the realm of public affaires. Thus, his intellectual career and his political propositions have intertwined many times during the years of his activity without, however, any of them being dependent of the other. Our perspective intends to highlight not only the relationships between these two levels but also their spaces of possible autonomy, their gaps, tensions and conflicts. Herrera’s case is here examined as a form of a broader interrogation over the conditions of exercise concerning the intellectual activity of his time.